Presupposition in Haters’ Comments on Joe Biden’s Instagram Posts - Dewi, Novita (Journal of Literature, Linguistics, & Cultural Studies, 2024)
This study discusses the presupposition expressed by haters of Joe Biden’s Instagram account. The aim of this research is to find out the types of presupposition in haters' comments on Joe Biden’s posts on his Instagram account and the implicit meaning of the presupposition. This research uses the theory of Huang (2014) for the presupposition analysis and the theory of Larson (1984) for the implicit meaning. This study used the descriptive qualitative method because the researcher can find out the perspective of the object of research more deeply that cannot be represented by statistical figures. The data obtained from the utterances of haters in the comment column of Joe Biden’s Instagram account, then it was classified by types and then interpreted in the implicit meaning of the utterances. The source of the data was taken from two posts about the G20 posted by Joe Biden on 17, November 2022 in his Instagram account. In the results of this study, the researcher found seven (7) types of presupposition based on data source 1 and data source 2. They are definite description, aspectual, iterative, implicative predicates, quantifier, temporal clause, and counterfactual conditional. The type most commonly found in this study is definite description. The researcher also found the kinds of implicit meaning to interpret the presupposition. They are implicit referential meaning, organizational meaning, and situational meaning. Implicit organizational meaning is the kind of implicit meaning that is often used by haters in the comments column on Joe Biden’s Instagram account. For future researchers, this research can be used as a reference for carrying out research, especially those related to presupposition according to Yan Huang.